BRICS SIX AND THE HEGEMONIC STABILITY THEORY - Setiawan, Dani; Alatas, Muhammad Salim; Dinda Azalia, Nathaniela (Lintas Cendekia Publishing, 2023)
This research is focusing to identify BRICS SIX as a potential hegemon in the form of institution rather than a dominant country in the theory of hegemonic stability. Singular dominant power in the political, economic and military according to hegemonic stability theory can ensure the stability of the international system. Surely this gap is fruitful to understand more regarding the United States dominant power are being challenge by the BRICS SIX member countries as a multipolar in terms of hegemonic stability. By using a qualitative method, this research finds that China is the dominant power economically within the BRICS, yet the power are being transmitted to multipolar towards the member country. For example, the new gold standard of the BRICS, are proposed to the global world as an institutional rule, rather than promoting China renminbi.